Effect of Age and Number of Seedlings along with Interculturing Practices on Growth and Yield of Transplanted Paddy - Sinha, S.K.; Sahai, R.N.; Srivastava, V.C. (Journal of Soil and Water Conservation, 2022)
It is vital importance to adopt sound cultural practices to step up the production of rice.4The cultural treatment which the crop receives during the various growth phases have an important bearing in influencing the internal physicochemical changes. They constitute the vital activities of the plant leading upto the manifestation of the yield attributes as tillering, panicle number, ear head size etc., which mainly determine the ultimate yield of the crop. in order to study the effect of age of paddy seedlings for transplanting, number of seedling per hill and stirring the soil in transplanted field on growth and yield of late aman paddy (BRS), an experiment was conducted during the kharif season of 1965-66 at Ranchi Agricultural College Farm, Kanke.